Effect of Sowing Depth on the Yield of Spring Wheat - Alam, MS; Sultana, MS; Hossain, MB; Salahin, M; Roy, UK (Journal of Environmental Science and Natural Resources, 2015)
The experiment was conducted to study the effect of sowing depth on the yield of spring wheat. The experiment consisted of two factors i.e. three sowing depth viz. 2 cm, 4 cm, 8 cm and two modern wheat varieties viz. Bijoy and Prodip. A randomized complete block design was adopted with three replications. Results indicated that the effect of sowing depth was significant on almost all the parameters except spike length. Sowing on 4 cm depth gave the highest grain yield (3.88 t ha-1) followed by 2 cm (3.75 t ha-1) and 8 cm sowing depth (3.62 t ha-1). Significant variation was found due to different varieties in respect of all the parameters studied. Bijoy produced the highest grain yield (3.92 t ha-1) and the lowest one was produced by Prodip (3.57 t ha-1). Bijoy produced the highest grain yield (4.06 t ha-1) when sown on 4 cm depth. DOI: http://dx.doi.org/10.3329/jesnr.v7i1.22184 J. Environ. Sci. & Natural Resources, 7(1): 277-280 2014